PENGARUH MODEL PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS XI IPA MADRASAH ALIYAH SYEKH YUSUF SUNGGUMINASA (STUDI PADA MATERI LARUTAN ASAM DAN BASA) - Felly Falentina Adam (Program Pasca Sarjana UNM, 2017)
The learning model which always used by the teacher was direct learning model with teacher centered characteristic, nowdays the learning model which was more suggested was student centered learning model which centered to the students such as Problem Based Learning (PBL). The choosing of the right model, should considered the students psychology condition such as learning motivation which encouraged the learning process, so the learning result could be maximal. The research was Queasy Experiment which involved two classes XI IPA which consisted of 36 students with factorial design 2 x 3. The data was obtained through learning motivation questionnaire and learning result test which analyzed by using SPSS 21 application through Two Way Anova test with mistake level 5% (α = 0,05). The result of research showed that (i) there was a difference of the students’ learning result after being taught by using PBL and direct learning model; (ii) there was no difference of learning result of the students who had high, medium and low motivation; and (iii) there was a difference of learning result of the students who had high, medium and low motivation after taught by using PBL model and direct learning model.